Ultrafast Charge Transfer on Ru‐Cu Atomic Units for Enhanced Photocatalytic H2O2 Production - Feng, Chengyang; Alharbi, Jumanah; Hu, Miao; Zuo, Shouwei; Luo, Jun; Qahtani, Hassan S. Al; Rueping, Magnus; Huang, Kuo‐Wei; Zhang, Huabin (Advanced materials (Weinheim), 2025)
Photosensitizer‐assisted photocatalytic systems offer a solution to overcome the limitations of inherent light harvesting capabilities in catalysts. However, achieving efficient charge transfer between the dissociative photosensitizer and catalyst poses a significant challenge. Incorporating photosensitive components into reactive centers to establish well‐defined charge transfer channels is expected to effectively address this issue. Herein, the electrostatic‐driven self‐assembly method is utilized to integrate photosensitizers into metal–organic frameworks, constructing atomically Ru‐Cu bi‐functional units to promote efficient local electron migration. Within this newly constructed system, the [Ru(bpy)2]2+ component and Cu site serve as photosensitive and catalytic active centers for photocarrier generation and H2O2 production, respectively, and their integration significantly reduces the barriers to charge transfer. Ultrafast spectroscopy and in situ characterization unveil accelerated directional charge transfer over Ru‐Cu units, presenting orders of magnitude improvement over dissociative photosensitizer systems. As a result, a 37.2‐fold enhancement of the H2O2 generation rate (570.9 µmol g−1 h−1) over that of dissociative photosensitizer system (15.3 µmol g−1 h−1) is achieved. This work presents a promising strategy for integrating atomic‐scale photosensitive and catalytic active centers to achieve ultrafast photocarrier transfer and enhanced photocatalytic performance. [Ru(bpy)2]2+ photosensitive components are integrated into the Cu‐HHTP MOF, coordinating with the Cu‐O4 sites to assemble a bi‐functional unit, thereby facilitating efficient local electron migration. Compared to the dissociative photosensitizer system, this newly constructed configuration exhibits a significant increase in the efficiency of photoinduced charge carrier transfer, resulting in a 37.2‐fold enhancement in the photosynthesis of H2O2.